Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Certainly! Let's solve the given quadratic equation step-by-step and find the value of [tex]\( r \)[/tex], the sum of the solutions.
The quadratic equation given is:
[tex]\[ x^2 - 14 = 2 \][/tex]
First, we need to rearrange this equation into standard quadratic form [tex]\( ax^2 + bx + c = 0 \)[/tex].
[tex]\[ x^2 - 14 - 2 = 0 \][/tex]
[tex]\[ x^2 - 16 = 0 \][/tex]
We identify that the equation is now in standard quadratic form, where:
[tex]\[ a = 1, \quad b = 0, \quad c = -16 \][/tex]
Next, we factor the quadratic equation:
[tex]\[ x^2 - 16 = (x - 4)(x + 4) = 0 \][/tex]
Setting each factor equal to zero gives us the solutions:
[tex]\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \][/tex]
[tex]\[ x + 4 = 0 \quad \Rightarrow \quad x = -4 \][/tex]
Now we have the solutions [tex]\( x = 4 \)[/tex] and [tex]\( x = -4 \)[/tex].
To find the sum of the solutions, we simply add them together:
[tex]\[ 4 + (-4) = 0 \][/tex]
Therefore, the value of [tex]\( r \)[/tex], the sum of the solutions, is:
[tex]\[ r = 0 \][/tex]
So, the correct answer is:
[tex]\[ \boxed{0} \][/tex]
This confirms that the value of [tex]\( r \)[/tex] is indeed [tex]\( 0 \)[/tex].
The quadratic equation given is:
[tex]\[ x^2 - 14 = 2 \][/tex]
First, we need to rearrange this equation into standard quadratic form [tex]\( ax^2 + bx + c = 0 \)[/tex].
[tex]\[ x^2 - 14 - 2 = 0 \][/tex]
[tex]\[ x^2 - 16 = 0 \][/tex]
We identify that the equation is now in standard quadratic form, where:
[tex]\[ a = 1, \quad b = 0, \quad c = -16 \][/tex]
Next, we factor the quadratic equation:
[tex]\[ x^2 - 16 = (x - 4)(x + 4) = 0 \][/tex]
Setting each factor equal to zero gives us the solutions:
[tex]\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \][/tex]
[tex]\[ x + 4 = 0 \quad \Rightarrow \quad x = -4 \][/tex]
Now we have the solutions [tex]\( x = 4 \)[/tex] and [tex]\( x = -4 \)[/tex].
To find the sum of the solutions, we simply add them together:
[tex]\[ 4 + (-4) = 0 \][/tex]
Therefore, the value of [tex]\( r \)[/tex], the sum of the solutions, is:
[tex]\[ r = 0 \][/tex]
So, the correct answer is:
[tex]\[ \boxed{0} \][/tex]
This confirms that the value of [tex]\( r \)[/tex] is indeed [tex]\( 0 \)[/tex].
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.